Roadmap of Excise on Cigarette Policy Package in Indonesia: an Analytical Hierarchy Process Approach - Syaifudin, Noor (Journal of Social and Development Sciences, 2013)
On national budget, the revenue from excise is keeping to increase as the consumption level of cigarette tends to increase as well. The need of high revenue to satisfy the expenditure will tend to force the government to keep this industry to be existed. However, the potential loss of the state revenue caused by the illicit products is threatening. This study attempts to address this policy problem by providing policy recommendations based on in-depth analysis and evaluation of the policy alternatives. The Analytical Hierarchy Process employed to obtain quantitative measurement of the analysis. As the need of the state revenue to satisfy the national budget, thus the high excise revenue will be required, whilst on the other side the consumption of cigarette needs to be controlled. This confirms that the increase in excise rate will affect in curbing the cigarette consumptions. As several stakeholders will be impacted in the reduction its economic output to the overall economy, thus the Government of Indonesia need to shift this impacted industries to other sectors which will obtain a better output. Finally, this paper recommends an integrated roadmap of excise policy package for controlling the cigarette consumptions in order to satisfy and ensure the national budget, curbing the cigarette consumption and managing the cigarette industries. The proposal comprises of: increasing the excise tariff, encountering the illicit cigarette, simplifying the cigarette industry structure, non tariff policy, introducing new potential excised objects, and shifting the impacted sectors.